Analisis Interaksi Pengguna dalam Desain User Interface dan User Experience yang Lebih Baik Menggunakan Metode Heuristik - Septiani Kurnia; Nur Nawaningtyas (Pusat Riset dan Inovasi Nasional, 2024)
Effective User Interface (UI) and User experience (UX) design relies heavily on good interactions between users and the system. One approach to improving the quality of these interactions is to use heuristic methods. This method allows designers to spread the usability of an interface based on certain principles, such as readability, consistency, feedback, and efficiency. This study reviews how heuristic methods can be applied to identify potential problems in UI/UX design and provide solutions to create a better user experience. By transmitting designs through heuristic criteria, designers can quickly find errors that may not be visible in conventional trials, thereby accelerating system improvement and refinement. In addition, user interaction analysis through this method also provides a more systematic guide to designing UI/UX that is responsive to user needs, both visually and functionally. This study highlights the importance of using interactive heuristic evaluation in the product development cycle to ensure optimal user experience quality. The results of applying this method show increased navigation efficiency, better user engagement, and decreased user error rates.